2017
DOI: 10.1177/0956797617692108
|View full text |Cite
|
Sign up to set email alerts
|

Political Orientation Predicts Credulity Regarding Putative Hazards

Abstract: 23 24 25 26 The instruments described in this paper are included in the Supplementary Online Materials, and 27 are also archived at osf.io/qqq82. The complete datasets, lists of variables, and analytic code are 28 archived at osf.io/qqq82 and http://escholarship.org/uc/item/82j5p9r3 29 Accepted for publication in Psychological Science 1 Abstract 30To benefit from information provided by others, people must be somewhat credulous. However, 31 credulity entails risks. The optimal level of credulity depends on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 35 publications
5
78
0
2
Order By: Relevance
“…This supports the view that conservative minds are particularly prone to worldview effects when processing contentious information (Jost, ; Jost et al, ; Nam et al, ; Prasad et al, ). This might best be explained by the notion that worldview effects are mediated by the negative emotional impact of self‐concept threatening corrections, combined with the assumption that conservatives are (1) particularly susceptible to such threats (Carraro et al, ; Fessler et al, ; Hibbing et al, ; Trevors et al, ) and (2) generally less likely to engage with worldview‐dissonant information based on their greater need for certainty, ambiguity intolerance, and closed‐mindedness (Carney et al, ; Fibert & Ressler, ; Jost, ; Price et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports the view that conservative minds are particularly prone to worldview effects when processing contentious information (Jost, ; Jost et al, ; Nam et al, ; Prasad et al, ). This might best be explained by the notion that worldview effects are mediated by the negative emotional impact of self‐concept threatening corrections, combined with the assumption that conservatives are (1) particularly susceptible to such threats (Carraro et al, ; Fessler et al, ; Hibbing et al, ; Trevors et al, ) and (2) generally less likely to engage with worldview‐dissonant information based on their greater need for certainty, ambiguity intolerance, and closed‐mindedness (Carney et al, ; Fibert & Ressler, ; Jost, ; Price et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative position has highlighted individual differences in personality traits between left‐leaning progressives and right‐leaning conservatives and has claimed that these differences underlie biases in information processing (Feather, ; Jost, ; Jost, Glaser, Kruglanski, & Sulloway, ; Mooney, ; Thórisdóttir & Jost, ). There is ample evidence that conservatives exhibit greater levels of negativity bias and perceived threat (e.g., Carraro, Castelli, & Macchiella, ; Fessler, Pisor, & Holbrook, ; Hibbing, Smith, & Alford, ) as well as greater need for certainty and ambiguity intolerance (e.g., Fibert & Ressler, ; Jost, ) and lower open‐mindedness (e.g., Carney, Jost, Gosling, & Potter, ; Price, Ottati, Wilson, & Kim, ). Jost and colleagues (Jost, ; Jost et al, ) argue that attitudes and beliefs are not, as suggested by the cultural cognition thesis, passively absorbed from one’s sociocultural context, but that an individual tends to actively adopt attitudes that resonate with their personality.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with CMSC, experimental evidence indicates that "negative information [in the form of unpleasant words or pictures] exerts a stronger automatic attention-grabbing power in the case of political conservatives, as compared to liberals" (Carraro et al 2011, p. 5). Fessler et al (2017) found that conservatives were more likely than liberals to rate false statements about potential hazards as credible in comparison to false statements about potential benefits. Other research shows conservatives to be more sensitive to disgust than liberals, a difference that translates into more severe moral judgments among conservatives on a range of sociocultural issues (Inbar et al 2009;Inbar et al 2012;Eskine et al 2011;Smith et al 2011).…”
Section: Of 25mentioning
confidence: 95%
“…Given the functional associations between i) perceptions of the world as dangerous and the value of enhanced negatively-biased credulity, and ii) social conservatism and perceptions of the world as dangerous, it follows that social conservatives should exhibit greater negatively-biased credulity than social liberals. Fessler, Pisor, and Holbrook (2017) tested this prediction by employing the paired-statements measure of negativelybiased credulity described earlier in conjunction with a variety of existing measures of political orientation. In two studies of Americans, the authors found that, per predictions, social conservatism was positively correlated with negatively-biased credulity.…”
Section: Evidence Of Negatively-biased Credulity and Informational Nementioning
confidence: 99%
“…As a consequence, we can expect natural selection to have shaped the human mind so as to make people more credulous of information concerning hazards than of information concerning benefits, i.e., to exhibit negatively-biased credulity (Fessler et al, 2014;Fessler, Pisor, & Holbrook, 2017).…”
mentioning
confidence: 99%